2002
DOI: 10.1038/emm.2002.35
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ca(2+) in diallyl disulfide-induced apoptotic cell death of HCT-15 cells

Abstract: Diallyl disulfide (DADS) induced apoptosis through the caspase-3 dependent pathway in leukemia cells was earlier reported from this laboratory. In this study, we investigated the involvement of Ca 2+ in DADS-induced apoptotic cell death of HCT-15, human colon cancer cell line.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
40
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(46 citation statements)
references
References 35 publications
5
40
0
Order By: Relevance
“…22,23,24 Both pathological increase of Ca 2 þ concentration in the cytosol compartment by inophores 25 and depletion of intracellular Ca 2 þ stores may trigger apoptosis by disrupting intracellular architecture and allowing effectors to gain access to their substrates. 24,26,27 Activation of apoptotic endonucleases 28 eliciting DNA cleavage and chromatin condensation has been well documented. 29,30,31 A tight buffering of intracellular Ca 2 þ is required for normal growth.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…22,23,24 Both pathological increase of Ca 2 þ concentration in the cytosol compartment by inophores 25 and depletion of intracellular Ca 2 þ stores may trigger apoptosis by disrupting intracellular architecture and allowing effectors to gain access to their substrates. 24,26,27 Activation of apoptotic endonucleases 28 eliciting DNA cleavage and chromatin condensation has been well documented. 29,30,31 A tight buffering of intracellular Ca 2 þ is required for normal growth.…”
mentioning
confidence: 99%
“…29,30,31 A tight buffering of intracellular Ca 2 þ is required for normal growth. In fact, apoptosis can be induced by Ca 2 þ mobilization from intracellular pools, 23,24,27 chelation of intracellular Ca 2 þ with 1,2-bis-(2-aminophenoxy)ethane-N,N,N 1 ,N 1 -tetra-acetic acid tetra-acetoxymethyl ester (BAPTA-AM) 28,29 or removal of extracellular Ca 2 þ . 32 Intracellular Ca 2 þ deficiency regulates gene expression 22,26 and induces apoptosis through caspases activation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…recent studies have reported that the ability of dadS to up-or down-regulate the mrna expression of some genes is related to its signal pathway (17)(18)(19)(20)46). our results revealed that dadS may be involved in mediating multiple signal pathways in HT-29 cells by up-regulating the expression of GPCR175, GNB1, PSMD12, S100A6, TACSTD2 or by suppressing ATP1A1, YWHAE and FLJ25150 fis.…”
Section: Discussionmentioning
confidence: 55%
“…dadS induces the elevation of cytosolic ca 2+ and activates the cell apoptotic program (18,19). in the present study, four genes, including S100 a6, TacSTd2, PABP (found in DHUG) and DNCL1 (found in DHDG), were potentially related to cell apoptosis and cytosolic ca 2+ .…”
Section: Discussionmentioning
confidence: 99%